2018
DOI: 10.1136/annrheumdis-2018-213511
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1 improves the Treg/Th17 imbalance in rheumatoid arthritis through miR-21

Abstract: MaR1 is a therapeutic target for RA, likely operating through effects on the imbalanced Treg/Th17 ratio found in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 37 publications
5
96
0
2
Order By: Relevance
“…In FLS of RA patients, miRNA-23b can regulate arthritic inflammation by inhibiting the NF-κB signal pathway [16]. Furthermore, SPMs can regulate the Treg/Th17 imbalance in CIA mice by upregulating miR-21 [17]. These studies indicate that RvD1 is apt to exert its biological functions through microRNA.…”
Section: Introductionmentioning
confidence: 85%
“…In FLS of RA patients, miRNA-23b can regulate arthritic inflammation by inhibiting the NF-κB signal pathway [16]. Furthermore, SPMs can regulate the Treg/Th17 imbalance in CIA mice by upregulating miR-21 [17]. These studies indicate that RvD1 is apt to exert its biological functions through microRNA.…”
Section: Introductionmentioning
confidence: 85%
“…In T lymphocyte progenitors, such mechanism would drive differentiation of T lymphocytes towards the anti‐inflammatory regulatory T cells phenotype (Melnik & Schmitz, ). This would, therefore, explain the beneficial role of milk EVs observed on rheumatoid arthritis (Arntz et al., ) for which a lymphocyte Th17/Treg balance is of prime importance and can be modulated by microRNAs (Jin et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 97%
“…Maresin (MaR) family is a newly described macrophagederived mediator of inflammation resolution [7]. MaR1 is the first reported member of this family and shows broad antiinflammatory actions under physiologic conditions in endothelial cells and vascular smooth muscle cells [8], human periodontal ligament cells [9], and has been reported to have benefits on multiple diseases, such as acute pancreatitis [10], neurocognitive disorders [11], and inflammatory arthritis [12]. More important, recent studies also revealed that MaR1 play roles in obesity [13] and nonalcoholic steatohepatitis [14], indicating a strong association between MaR1 and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%